An Atypical Case of Latent Autoimmune Diabetes of Adults - Kim, Keun Young (J Endocr Soc, 2021)
Introduction: Latent autoimmune diabetes of adults (LADA) is an adult-onset, slowly progressing subtype of autoimmune type 1 diabetes mellitus (T1DM), that is often misdiagnosed as T2DM. We present an atypical case of LADA that was presented in an uncommonly late age with high titres of anti-glutamic acid decarboxylase antibodies(GADA). Clinical Case: A 78 year old male presented with alcohol intoxication and hyperglycemia. His serum glucose was 441mg/dL with negative urine ketones. Arterial blood gas showed pH 7.36, HCO3- 20mmol/L, pCO2 37.1mmHg. Anion gap was 11. HbA1c level was 16%. His body weight was 43.2kg with a BMI of 16.6. He was having polyuria and polydipsia, and was recently diagnosed with T2DM. His low BMI and symptoms raised suspicion for LADA. GADA titres revealed to be greater than 250IU/mL. A diagnosis of LADA was made. He was discharged on insulin. Conclusion: LADA shares the same genetic and autoimmune profiles with T1DM, but its insidious presentation overlaps with that of T2DM, often delaying diagnosis and adequate treatment. Our case of confirmed LADA at a late age of 78 is atypical, but warrants that adults newly diagnosed with diabetes should be screened for LADA if there are atypical findings. Among the anti-islet antibodies, GADAs are the most sensitive self antigen-antibody markers of autoimmune diabetes. The GADA titre is often used to stratify the risk of progression to insulin dependence in LADA, as a higher titre suggests severe β-cell loss in the pancreas. High GADA titres at the time of diagnosis at an elderly age is also an uncommon finding for LADA. Autoimmune diseases with aggressive autoimmune responses present early, while indolent progressions lead to late onset of symptoms and diagnosis. Thus it is unusual for our patient to have significantly high GADA levels. As pathophysiology of LADA is yet to be understood, further research may reveal the autoimmune process of GADA and the role of titres in disease activity and progression. There are no current therapeutic guidelines for LADA. Our patient was eventually discharged on insulin given his high HbA1c with high titres of GADA, but there were questions regarding the use of oral glycemic control agents due to his history of noncompliance. The use of oral agents for LADA remains an area of ongoing research. The general understanding is that due to its autoimmune etiology, insulin is eventually required. Early insulin therapy preserves residual β-cell function, improves glycemic control, and reduces the risk of long-term complications. As treatment goals of LADA would be to improve glycemic control with preserving residual β-cell function, further research may establish treatment guidelines for LADA. Monitoring anti-islet antibodies and c-peptide titres may play a role in establishing the timing to introduce oral agents and/or insulin for optimal treatment of LADA.